Managing Your Florida Lawn Under Drought Conditions - Harold C. Jones; Charles Steven Lippi; Laurie E. Trenholm (EDIS)
Revised! ENH 157, a 3-page fact sheet by Harold C. Jones, Charles Steven Lippi, and Laurie E. Trenholm, Ph.D., provides homeowners with practices to follow to ensure a healthy lawn under restricted watering conditions. This version is updated throughout and includes a table of days between waterings for St. Augustinegrass lawns. Published by the UF Department of Environmental Horticulture, April 2006.